Acute exposure to a 2 mT static magnetic field affects ionic homeostasis of in vitro grown porcine granulosa cells. Issue 3 (16th January 2014) - Bernabò, Nicola; Saponaro, Ilaria; Tettamanti, Enzo; Mattioli, Mauro; Barboni, Barbara
<x xml:space="preserve">Abstract</x> In this work, we provided direct evidence for the first time that exposure to a static magnetic field (SMF) of low intensity (2 mT) is immediately followed by a reversible cell membrane depolarization wave (of about 1 min) that causes the rise of intracellular calcium and the decrease of mitochondrial activity of vital granulosa cells. These effects are likely due to the increase in Na+ and Ca2+ cell membrane permeability. Bioelectromagnetics. 35:231–234, 2014. © 2014 Wiley Periodicals, Inc.